Effects of Activity Schedules on Challenging Behavior for Children with Autism - Scalzo, Rachel; Davis, Tonya N.; Weston, Regan; Dukes, Elizabeth; Leeper, Dana; Min, Nandar; Mom, Allen; Stone, Jessica; Weber, Alex (Journal of the American Academy of Special Education Professionals, 2017)
This study examined activity schedules as an intervention to decrease challenging behavior and increase academic engagement during work tasks scheduled after free play activities in three boys diagnosed with autism spectrum disorder (ASD). Functional analysis results indicated all participants’ challenging behavior was maintained, at least in part, by access to tangibles. No differences were noted in challenging behavior nor in academic engagement between baseline and activity schedule conditions. Results suggest that activity schedules are not effective as a stand-alone intervention for children with ASD with tangibly maintained challenging behavior.